Trajectories to high income: comparing the growth dynamics in China, Korea, and Japan with cointegrated VAR models - Michael Murach; Helmut Wagner; Jungsuk Kim; Donghyun Park (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2020)
We analyze and compare the patterns of economic growth and development in China, Korea, and Japan in the post-war period. The geographical proximity and cultural affinity between the three countries, as well as the key role of the development state in the economies, suggest that an analytical comparison would be a meaningful and valuable exercise. Furthermore, Korea and Japan are two of the few economies that have jumped from middle income to high income in a short period and thus offer potentially valuable lessons for China. China is following a structural change that Korea and Japan underwent decades ago. We use Cobb–Douglas production functions to assess the long-run equilibrium relationships between per capita GDP, capital, and labor as well as the features of structural change by means of cointegrated vector autoregressive (CVAR) models. We show that such equilibrium relationships cannot be rejected for all three countries, while the evidence is stronger for China and Korea than for Japan. Our hypothesis tests show that the estimated Cobb–Douglas production functions display coefficients of capital and employment that sum up to one and broken linear trends that can be attributed to structural breaks and (changes in) total factor productivity (TFP) growth. We observe a striking similarity between the Korean and the Chinese experience, which gives some optimism that China may be capable of graduating to high income, like Korea.
urn:nbn:de:hbz:708-dh10395
Keywords: E23; O47; O53; O57; P52; 330; aggregate production function; comparative economic growth; China; Korea; Japan; economic development